Chronic Pain in Hansen’s Disease – A Public Health Problem? - R N A G Stump, Patrick (2006)
Hansen’s disease, which still shows high detection rate in Brazil, features peripheral nerve involvement and skin lesions  with sensory loss. The latter is one of the paradigms to the diagnosis of the disease. However, pain is a symptom that is  being increasingly reported in theses cases. Pain can be nociceptive due to tissue inflammation (reversal reaction and  erythema nodosum leprosum) and neuropatic (due to anatomical and/or functional damage to the nervous system). Fifty  three cases with complaint of pain were studied regarding spatial, temporal, defining, affective and evaluative  characteristics. Among them, 73.6% had completed their MDT/WHO treatment and 84.9% were multibacilary cases.  The spatial localization of pain was more prevalent to the ulnar and tibial nerves. Burning pain was the free description  referred by 28.3% of cases and the affective and evaluative adjectives used reveal a potential interference in the quality  of live of these individuals. Pain in Hansen’s disease cases can be present even after completion of treatment with  sensory, spatial, temporal and affective characteristic that are quite definite and hazardous, which demands control and  proper treatment.